Herramientas sencillas de análisis financiero. Ideas para su implementación en Pymes de San Miguel, Provincia de Buenos Aires - Larretape, Gabriel A. (2019)
In Argentina, SMEs have a fundamental importance in the economic and labor development of the country, developing within an unstable environment that, for different aspects, are maintained over time. In this way, the SME entrepreneur develops a culture characterized by day-to-day management, lack of long-term planning, non-delegation of tasks, lack of relevant information, risk aversion and other deficiencies that impact in a negative way - in decision making and - by optimization - in the creation of value in the company. The aspects described above include the relevance of carrying out works that contribute to its solution and the proposal of tools that contribute to the flow of relevant information and - in this way - to the strengthening of Argentine SMEs. Based on what has been previously developed, the relevance of the hypothesis -which is not corroborated- can be taken, which suggests that the implementation or strength of HFS can provide relevant information for decision-making and value creation in the SME of San Miguel , Buenos Aires, Argentina. To this end, HFS and its applicability in SMEs in the geographic area described have been studied. A descriptive exploratory study has been carried out, with a qualitative quantitative methodology and qualitative predominance. The research design has been non-experimental and - within them - transversal and case.